Sikap Bahasa Generasi Muda Jawa terhadap Ragam Bahasa Jawa Krama Madya - Munawwir Hadiwijaya; Yahmun Yahmun; Suhartatik Suhartatik (IKIP Budi Utomo Malang, 2022)
The purpose of this study is to determine the language attitude of the younger generation of Javanese in the city of Malang to the variety of Javanese Krama Madya. Data were obtained from young Javanese aged 17-27 years who live in Malang City with various backgrounds, ranging from students, teachers, government agency employees to traders, by distributing questionnaires, interviews, and direct observations in the field. The data obtained will be analyzed using a tripartite structure of attitudes: cognitive, affective, and behavioral, which are reflected in two language attitudes, namely attitudes towards the language which emphasize a sense of responsibility and respect for language, and language attitudes which emphasize language mastery and orderly use of language. Of the eight indicators used to determine language attitudes, six showed negative attitudes, while only two were positive).